ANTI-HELICOBACTER PYLORI ACTIVITY AND IMMUNOSTIMULATORY EFFECT OF OLIGOSACCHARIDE ISOLATED FROM AVERRHOA CARAMBOLA L. - W, KAPFO; JB, CHAUHAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main goals of the study were to isolate oligosaccharide as a secondary metabolite from indigenous fruit, Averrhoa carambola L. (star fruit), and analyze its anti-Helicobacter pylori and immunostimulatory potential. Methods: The oligosaccharide (S3W) isolated using adsorption chromatography was partially characterized using tandem mass spectrometry in atmospheric pressure chemical ionization/electron spray ionization (APCI/ESI) positive and negative mode and nuclear magnetic resonance. The use of microtiter well method determined anti-H. pylori activity in the form of percentage inhibition of microbial growth, while the determination of the immunostimulatory potential of S3W implemented a protection of DNA, buccal cells, and macrophages against damage by oxidant and N-nitroso-N- methylurea (MNU) and percentage splenocyte proliferative potential. Results: S3W was a (1→2) β-heptaglucosaccharide with (4→6) α-branching at every second residue. APCI/ESI-positive mode showed B and A fragmentation patterns, while the negative mode showed abundance of A and C fragments. Anomeric hydrogen displayed integration values at 4.8 and 4.2 ppm indicating the presence of α-glucopyranose and β-glucopyranose. The compound protected DNA from oxidant-induced fragmentation. It expressed anti-H. pyloric activity with an IC50 value of 10.71 μg/ml. At 20 μg/ml, S3W protected buccal cells and macrophages significantly from damage due to oxidants and MNU carcinogens, while >50% splenocyte proliferation was induced as compared to that of an untreated control group. Conclusion: Our studies constitute the first report on the significant immunostimulatory activity of the oligosaccharide isolated from star fruit. The study, thus, supports its application as a therapeutic potential in curbing gastric diseases caused by H. pylori.